Educational Thought Adian Husaini: Concepts and Practices - Muhammad Kholid; Nesia Andriana; Abdul Hayyie Alkattani; Wido Supraha (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2022)
Educating human beings to be a believer, righteous and noble is included in Indonesian educational orientation. Nonetheless, this objective has been eroded by materialistic culture, particularly in the education environment. There are evident efforts to westernize national education by adopting the western education model, which is secular. Adian Husaini is an education thinker who has been criticizing this phenomenon and offering a solution of an educational concept and application based on ethics. This paper employs a mixed research methodology. The research includes an analysis of the paper works of Adian Husaini and a field study at the At-Taqwa boarding school led by Adian Husaini. The research reveals that the educational concept of Adian involves placing ethics and novelty on top of knowledge. The concept also holds a knowledge hierarchy in which knowledge of fard al-ayn (legal obligations that must be performed by each individual Muslim) is higher than selected knowledge of fard al-kifayah (principle of communal obligation) which is relevant to community development. At-Taqwa boarding school has been successful in some aspects in implementing educational concepts based on ethics. To conclude, Adian Husaini's thinking of education is relevant to adopt as an alternative basis for formulating the roadmap of national education.